Effect of dietary supplementation of inulin with low and high concentrate diet on growth performance and nutrient digestibility in Barbari goats - KUMAR, ABHISHEK; FAHIM, AHMAD; KUMAR , AMIT; SINGH, D K; CHANDRA, GULAB; ALI, NAZIM; ROY, DEBASHIS; KUMAR, ANUJ (The Indian Journal of Animal Sciences, 2023)
This study aimed to determine the effect of dietary supplementation of inulin on growth performance, feed conversion and nutrient digestibility in Barbari goats fed high and low concentrate diet for a period of 90 days. Twenty four yearling female Barbari goats were randomly divided into four equal groups (n=6) according to average body weight (18.24±1.16 kg). Treated animals in Group 1 were fed low concentrate diet (LCD; concentrate roughage ratio 40:60) and Group 2 (LCIN) with 2% inulin supplementation (% DM basis). Similarly, Group 3 was fed high concentrate diet (HCD; concentrate roughage ratio 60:40) and Group 4 (HCIN) with 2% inulin supplementation. Results showed that average daily gain (ADG) and feed conversion efficiency (FCE) were higher in inulin supplemented groups than the non-supplemented group. There was no increase in mean live body weight (BW) and dry matter intake (DMI) with inulin supplementation either in LCD or HCD treatment groups.The mean body condition score (BCS) was also similar in all groups. However, faecal score (FS) was superior in inulin supplemented group observed after 30 days of feeding trial. There was significant improvement in the digestibility coefficient of crude protein and DCP intake. It was concluded that inulin supplementation either in high concentrate and low concentrate diet of growing goats resulted in improvement in growth performance, faecal score and nutrient digestibility.